Challenges and Opportunities in the Growh of Homoeopathy: Academia, Profession, Trade & Industry (Homoeopathy for All, 2026)
Challenges for Growth; Globally,  it is the 2nd most popular system  of medicines being used, after the  Conventional Medicine. Imbalance  between its potential, and accept ability. Gaps between the theoreti cal training and the practice. Re search oriented limited education.  Outdated teaching methods. Lack  of Integration. Disproportionate Job  Opportunities. Societal Perceptions.  Inter-system competition. Standard ization in medicines production, in cluding that of Raw Material. Glob ally acceptable regulations and their  compliance. Harmony imbalance  between profession, Academics &  Industry. Encouraging entrepreneur ship. Way forward, with active participation, and collaboration.
Keywords: Challenges, popularity, imbalances, theory & practice, research, teaching methods, perceptions, competition, regulations, forward, participation, collaboration.